Salim's Clinical Management of Pain - Salim, M. (Brigadier); Edited By Salim, M. Dr. and Foreword By Melzack, Ronalo (Rawalpindi The Army Press, 1994)
Components people are suffering from pain. When pain becomes a constant problems it can be more malignant that any malignant disease.
Include Index, Glossary and Illustrations.
Keywords: Pain--Treatment -- Bones -- Diseases -- Treatment